Using Malarial Retinopathy to Improve the Diagnosis of Pediatric Cerebral Malaria - Lin, Yuzhou; Tebulo, Andrew; Small, Dylan; Seydel, Karl; Taylor, Terrie; Zhang, Bo (The American journal of tropical medicine and hygiene, 2023)
In malaria endemic areas, a high proportion of children have detectable parasitemia but show no clinical symptoms. When comatose from a cause other than malaria, this group confounds the cerebral malaria (CM) definition, making accurate diagnosis challenging. One important biomarker of CM is malarial retinopathy, a set of specific features visible in the ocular fundus. In this study, we quantified the contribution of malarial retinopathy in discriminating malaria-caused coma from non–malaria-caused coma. We estimated that 10% of our study cohort of N = 1,192 patients who met the WHO clinical definition of CM in Malawi had non-malarial coma based on a Gaussian mixture model using the parasite protein Plasmodium falciparum histidine-rich protein-2. A classification based on platelets, white blood cells, and retinopathy significantly improved the discriminative power of a previously established model including only platelets plus white blood cells (area under the receiver operating characteristic curve: 0.87 versus 0.75, P value < 0.001). We conclude that malarial retinopathy is highly predictive of malaria-caused versus non–malaria-caused coma and recommend that an ocular funduscopic examination to determine malarial retinopathy status be included in the assessment of parasitemic comatose African children.